The Application of Restorative Justice For Perpetrators and Victims of Traffic Accidents at The Medan City Police - Pandiangan, Rodo Venesia H.; Marlina; Ekaputra, Mohammad (LOCUS MEDIA PUBLISHING, 2024)
Traffic accident rates continue to rise, causing material damage and casualties. Although regulated by Law No. 22 of 2009, case resolution processes are often ambiguous, with some cases being resolved through the judicial system and others through Restorative justice (RJ). This study employs both normative and empirical methods, including interviews at Polrestabes Medan, to assess the implementation of RJ, its legal basis, and the challenges faced. The results indicate that several regulations, such as Law No. 11 of 2012 and Police Chief Regulation No. SE/8/VII/2018, address RJ. However, challenges such as conflicts of interest, lack of cooperation between perpetrators and victims, and unclear legal frameworks hinder the effective application of RJ. The study recommends establishing clearer legal regulations for RJ in traffic accident cases and enhancing the functions of relevant institutions to address these issues at Medan City Police.